The concurrent development of spelling skills in two languages - Rhonda Joy (International Electronic Journal of Elementary Education, 2011)
The study reported on in this paper investigated the concurrent development of spelling in children learning two languages. The study compared over time and between languages the types of spelling errors made in English as a first language and French as a second. Fortyseven grade one English-speaking children completed an English and French spelling task in October and May of the school year. The study relied on a repeated measures design using 2- tailed paired sample t-tests at the beginning and end of the school year. Results revealed students made more basic spelling errors at the beginning of the year and more complex spelling errors at the end of the year in both French and English. Despite the lack of direct instruction in English, students’ English spelling skills developed over the course of the year suggesting that transfer of skills was occurring between languages.